REDESIGN PRODUK PECI MENGGUNAKAN METODE KANSEI ENGINEERING - Saeful Najib; Ida Betanursanti (Universitas Ahmad Dahlan Indonesia, 2017)
Peci is one of the typical Indonesian fashion products favored by men. Peci used for a purpose both official and unofficial purposes. Many people want a product that is more than the usual Peci both in terms of materials and motifs. The purpose of this study is to realize the expectations of customers and develop the better design of peci that fit to the customer's feelings. The method used in this study is Kansei Engineering. That is a method that uses image or feeling psychologically from the user of the product. Then observations is looking for Kansei words and samples of product, There are obtained 10 Kansei words that represent the feeling of customers and 5 sampels of products of craftsmen. Then conjoint analysis is use to get the value of the relationship between elements design and Kansei words. The results of conjoint analysis obtained that special Peci is peci with batik embroidery motif with price is Rp35.000,00 and made of quality velvet. That is the highest preference of most favored by respondents. Recommend the design of the peci that has been obtained is with first quality velvet, batik embroidery three-leaved vines, Lidded green six cmyk: 100, 0, 100, 0 velvet, black cmyk: 0,0,0, 100 Flowers, red cmyk: 0,100,100,0. Ventilated at the top with a semicircular, and use the cardboard inside the furing wrapped with satin lining.Keywords: Kansei engineering, Peci design, conjoint analysis